Inadvertent Leakage of Organisational Information through Online Social Networking - Abdul Molok, Nurul Nuha (2014)
The advent of online social networking (OSN) amongst employees represents new fundamental challenges to organisations. As employees are bringing their own mobile devices to the workplace, which allow them to engage in social media activities at for organisations to protect the confidentiality of their valuable information. anytime and anywhere, reported cases involving leakage of organisational information through OSN are on the rise. Despite its opportunities, OSN has the tendency to blur the boundaries between employees’ professional and personal use of social media, presenting security issues for organisations to protect the confidentiality of their valuable information.